On the nature of Hα emitters at z ∼ 2 from the HiZELS survey: physical properties, Lyα escape fraction and main sequence. Issue 2 (21st July 2015) - Oteo, I.; Sobral, D.; Ivison, R. J.; Smail, I.; Best, P. N.; Cepa, J.; Pérez-García, A. M.
Abstract : We present a detailed multiwavelength study (from rest-frame ultraviolet to far-infrared) of narrow-band selected, star-forming (SF) Hα emitters (HAEs) at z ∼ 2.23 taken from the High-Redshift(Z) Emission Line Survey (HiZELS). We find that HAEs have similar properties and colours derived from spectral energy distributions as sBzK galaxies, and probe a well-defined portion of the SF population at z ∼ 2. This is not true for Lyα emitters (LAEs), which are strongly biased towards blue, less massive galaxies (missing a significant percentage of the SF population). Combining our Hα observations with matched, existing Lyα data, we determine that the Lyα escape fraction ( f esc ) is low (only ∼4.5 per cent of HAEs show Lyα emission) and decreases with increasing dust attenuation, ultraviolet continuum slope, stellar mass and star formation rate (SFR). This suggests that Lyα preferentially escapes from blue galaxies with low dust attenuation. However, a small population of red and massive LAEs is also present, in agreement with previous works and indicating that dust and Lyα are not mutually exclusive. Using different and completely independent measures of the total SFR, we show that the Hα emission is an excellent tracer of star formation at z ∼ 2 with deviations typically lower than 0.3 dex for individual galaxies. We find that the slope and zero-point of the HAE main sequence at z ∼ 2 strongly depend on the dust-correction method used to recover the SFR, although they are consistent with previous works when similar assumptions are made.